A KPCA-BRANN based data-driven approach to model corrosion degradation of subsea oil pipelines. (March 2022) - Li, Xinhong; Jia, Ruichao; Zhang, Renren; Yang, Shangyu; Chen, Guoming
Highlights: A data-driven model is developed for predicting corrosion rate of marine oil pipelines. KPCA are integrated with BRANN to establish a new hybrid approach. The performance of the KPCA-BRANN model is better than BRANN alone and KPCA-LMANN. The proposed model can support digitization of subsea operations. Abstract: Corrosion is an important reason for the structural degradation of offshore oil pipelines, which may cause serious economic loss and environmental pollution. Nowadays the digitalized devices make a number of monitoring data become available. The prediction of corrosion degradation based on monitoring data becomes an efficient tool to prevent corrosion failure of offshore oil pipelines. This paper integrates KPCA and BRANN techniques to develop a novel data-driven model for corrosion degradation prediction of offshore oil pipelines. The model can eliminate the redundant information from the original monitoring data and improve the robustness by regularization constraints. KPCA is applied to reduce the dimension of the factors affecting pipeline corrosion, and the extracted principal components of corrosion variables are inputted in BRANN to build a corrosion degradation prediction model. The data with dimension reduction are divided into training set and validation set. The model is compared with BRANN alone and KPCA-LMANN model, which indicates KPCA-BRANN model presents superiority in the robustness and prediction accuracy ( MSE  = 0.46%; R 2 =0.99). The proposed model can be used as an online prediction module of digitized process safety system, and support the reliability assessment and maintenance planning of corroded subsea pipelines.